AB0856 Real-life effectiveness of infliximab in the treatment of ankylosing spondylitis over 3 years: The canadian experience. (23rd January 2014) - Rahman, P.; Bensen, W.; Shaikh, S.; Longo, N.; Sampalis, J.; Otawa, S.; Khalil, S.
Abstract : Objectives: Ankylosing Spondylitis (AS) is a chronic inflammatory disorder affecting as much as 1% of the general population. 1 The efficacy of Infliximab in the management of AS has been demonstrated in several controlled clinical trials with limited follow-up periods. Longitudinal observational studies assessing real-life effectiveness of anti-TNF agents are essential in order to demonstrate the true benefits. The objective of this study was to assess in Canadian clinical practice the 36-month outcomes in patients with AS treated with Infliximab. Methods: The data for this analysis were obtained from BioTRAC, an observational prospective registry of adult AS patients initiated on treatment with Infliximab since 2005 and managed as per routine care. Patients enrolled were biologic-naïve or had initiated treatment with a biologic for a period of <6 months prior to enrolment. Results: A total of 204 AS patients who had at least one follow-up assessment were included in this analysis, with a mean age of 46 years and mean disease duration since diagnosis of 10.6 years. Among these, 148, 83, and 46 had a 12-, 24-, and 36-month assessment, respectively. At the time of enrollment in the registry, mean (SD) patient parameters were: C-reactive protein (CRP) =1.7 (1.9) mg/dL, erythrocyte sedimentation rate (ESR) =26.9 (20.5) mm/hr, morning stiffness =75.9 (39.3) mins, health assessment questionnaire (HAQ) =1.1 (0.6), physician global assessment of disease activity (PGA) =67.2 (18.1), BASDAI =6.5 (2.1), BASFI =6.2 (2.4), and ASDAS =3.8 (0.9). By 6 months of treatment significant improvements (P<0.05) were observed in all clinical and patient outcome parameters studied, which were sustained over 36 months of treatment. By 6, 12, 24, and 36 months 58%/68%/76%/84% and 30%/38%/48%/45%, achieved Clinically Important Improvement in ASDAS (Δ≥1.1) and ASDAS Major Improvement (Δ≥2.0), respectively. The proportion of patients with very high disease activity (ASDAS >3.5) decreased from 64.2% at baseline to 7.9% at 36 months. Conclusions: The results of this Canadian, longitudinal, real-life observational study demonstrate that treatment with infliximab over three years is effective in reducing symptom severity and improving outcomes in patients with ankylosing spondylitis. References: Elyan M, Khan MA. Diagnosing ankylosing spondylitis. J Rheumatol 2006;33 Suppl 78:12-23. Disclosure of Interest: None Declared